2016
DOI: 10.1016/j.diabres.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes prevalence, awareness and treatment and their correlates in older persons in urban and rural population in the Astana region, Kazakhstan

Abstract: The large differences in all diabetes indices between urban and rural regions, if confirmed in larger studies, may suggest an impact of westernised and urbanised lifestyle as well as access to health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 28 publications
5
36
3
Order By: Relevance
“…According to the previously published analyses on diabetes and arterial hypertension [ 8 , 9 ] the subjects were invited to visit the polyclinic early in the morning after an overnight fast. The fasting status was self-reported by participants and recorded in the questionnaire.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previously published analyses on diabetes and arterial hypertension [ 8 , 9 ] the subjects were invited to visit the polyclinic early in the morning after an overnight fast. The fasting status was self-reported by participants and recorded in the questionnaire.…”
Section: Measurementsmentioning
confidence: 99%
“…The diabetes was classified as fasting plasma glucose (FPG) concentration more than or equal to 7.0 mmol/l (126 mg/dl) or self-reported diabetes medication use; the questionnaire did not specify the type of diabetes (I or II). The measurements and derived indices were described in detail previously [ 9 ].…”
Section: Measurementsmentioning
confidence: 99%
“…Firstly, the cross-sectional study design may not be appropriate way to estimate the causal relationships, yet the age of starting to brush the teeth or parent socio-demographic factors is likely to precede the development of the outcome, however we are less con dent about the remaining covariates. Secondly, the response rate in this study was moderate (68%), however many recent studies in both developed and developing countries reported roughly the same percentage (8,9,23,36). The moderate response rates may lead to both under-and overestimation of caries prevalence, but usually non-responders in dental health studies have poorer oral health than responders (37).…”
Section: Discussionmentioning
confidence: 52%
“…(6,7). Many of these risk factors might be related to societal changes after the collapse of the Soviet Union, when the newly independent states faced a rapid nutrition transition shifting towards westernized diets and increased consumption of sugar-added drinks and foods (8)(9)(10). The implications of these rapidly changing behaviours is not only the high prevalence, but also more severe dental caries experience (5,11).…”
Section: Introductionmentioning
confidence: 99%
“…This study is consistent with studies in Ethiopia, Myanmar, Iran, India, and Kazakhstan. 6,22,24,25,37 Affluent people live in urban areas, reducing the number of people living in traditional rural livelihoods, which might result in obesity associated with rising living standards. 1,6,25,38 Likewise, urban life is a more complicated, stressful, and competitive life compared with the rural ones.…”
Section: Discussionmentioning
confidence: 99%